Identification and characterization of HIV-specific RNase H by monoclonal antibody. - Hansen, J (1988)
Human immune deficiency virus (HIV) replicates by conversion of the RNA genome into the double-stranded DNA provirus. The reverse transcriptase is not the only enzymatic function crucial in DNA-provirus synthesis. A viral-coded RNase H activity which specifically degrades RNA in RNA-DNA hybrids has been shown to be essential as well. Here we demonstrate that the HIV-reverse transcriptase which consists of a two-polypeptide complex, p66 and p51, copurifies with an RNase H activity which exhibits properties of a processive exonuclease. Only the p66 molecule, not p51, is active as polymerase as evidenced by activated gel analysis. p66 exhibits RNase H activity when precipitated as immune complex by a monoclonal antibody raised against a bacterially expressed carboxy-terminal portion of p66. The monoclonal antibody which does not interfere with enzyme activity also precipitates a second population of molecules with RNase H activity which is of low mol. wt, p15. This RNase H appears therefore to be derived from the carboxy terminus of p66 during processing to the p51 polypeptide. It exhibits low template-binding ability and is of a non-processing mode of action which may be due to the absence of the reverse transcriptase domain. These results lend experimental support to the hypothesis that the RNase H gene maps at the carboxy terminus of the reverse transcriptase. Since both RNase H populations are virus-coded they may be essential for retrovirus replication in general and useful targets for chemotherapeutic agents.